Alveolar Septal Widening as an "Alert" Signal to Look Into Lung Antibody-mediated Rejection: A Multicenter Pilot Study. Issue 11 (November 2019) - Calabrese, Fiorella; Hirschi, Sandrine; Neil, Desley; Montero-Fernandez, Angeles; Timens, Wim; Verbeken, Erik; Chenard, Marie-Pierre; Ivanovic, Marina; Le Pavec, Jerome; Pena, Tahuanty; Dorfmüller, Peter; Roux, Antoine; et al.
Abstract : Background: Antibody-mediated rejection (AMR) plays an important role in allograft dysfunction. Acute lung injury (ALI), endotheliitis, capillary inflammation, and C4d positivity have been described as morphological features conventionally associated with lung AMR. A multidisciplinary, international task force reviewed AMR cases in the context of four face-to-face meetings. Septal widening was a frequent, striking histological feature recognized first and easily at low-power magnification. This study aimed to evaluate whether septal widening could represent an "alert" signal for AMR. Methods: Following the face-to-face meetings that enabled the classification of cases as AMR or non-AMR, morphometry was performed on biopsies from 48 recipients with definite, probable or possible AMR, 31 controls (negative for any posttransplant injury) and 10 patients with nonimmune-related ALI. Results: Mean alveolar septal thickness was greater in AMR patients than in controls ( P < 0.001). Septal thickness was not significantly different between AMR-ALI and non–AMR-ALI. Unexpectedly septal widening was the only histological change detected in some cases with probable or possible AMR that lacked the histological lesions conventionally associated with AMR. The thickness in these cases was similar to that observed in AMR cases with more severe histological injury such as ALI or neutrophilic capillaritis. Conclusions: Our data suggest that, even if unspecific as the other lesions conventionally associated with AMR, septal widening may represent an "alert" signal to look into lung AMR. A larger prospective study is mandatory to confirm the potential value of septal widening in the multidisciplinary approach of AMR. Abstract : Supplemental Digital Content is available in the text.